Rural–urban and age differences in association between depression and suicidal attempt: a large retrospective clinical sample study in China - Yong Xia; Dandan Ge; Zhonghua Zhang (BMJ Open)
Objectives To assess the association between depression and suicide attempt (SA) by age and region.Design Cross-sectional study.Setting First Affiliated Hospital of Wannan Medical College from January 2021 to January 2022.Participants Hospitalised patients.Primary outcome measures SA was the primary outcome and data on SA was obtained from the electronic medical records of hospitalised patients.Methods and analysis In this study, data on inpatients of the First Affiliated Hospital of Wannan Medical College from January 2021 to January 2022 were extracted from the medical record system using the convenience sampling method. According to the exclusion criteria, 7593 eligible research subjects were obtained. Logistic regression analysis was used to assess the association between depression and SA, combining age and region. Subgroup analyses were carried out to assess the relationship between age, region and SA in depressed patients, after excluding non-depressed patients, and to inspect the interaction of age and region. Finally, further comparisons of the disparities in suicide patterns among different age groups and regional groups were made.Results Among 7593 patients (3630 males), 655 (8.6%) patients with SA were observed. We found that depression was significantly associated with SA by age and region (all p<0.05). Specifically, depressed juveniles and adults had a higher risk of SA compared with non-depressed adults, and ORs (95% CIs) were 2.62 (1.59 to 4.30) and 1.67 (1.30 to 2.13), respectively. Furthermore, rural individuals with depression, urban individuals without depression and urban individuals with depression had a higher risk of SA compared with rural participants without depression, and ORs (95% CIs) were 1.60 (1.22 to 2.12), 1.29 (1.04 to 1.61) and 2.53 (1.83 to 3.49), respectively. In subgroup analyses, we further found that depression was strongly associated with SA in juveniles (OR 2.84, 95% CI 1.19 to 6.76, p=0.018) and urban patients (OR 1.67, 95% CI 1.15 to 2.40, p=0.006). Notably, the predominant methods of suicide among individuals with depression were the utilisation of sleeping pills or antidepressants.Conclusion Our study found individuals with depression are at higher risk of SA, especially juveniles and urban individuals. Effective integration of mental health and urban–rural services could mitigate the risk of suicide and contribute to better outcomes.